! ( ) ?





  • ▲ 
  • ◄ 
 > > > 7 > § 4

§ 4. .

.5xy² − 3yp³ + 4xy.
, , .x² + a; ax + 3,5c4.
, , .x + 5xy³ + 6.
.15d² m7 n.
, . × 5b + 3ab − b =
= 15ab + 3ab − b =
= 18ab − b.
.(2ab − 5c) + (3a² b + 3c) =
= 2ab − 5c + 3a² b + 3c =
= 3a² b + 2ab − 2c;

(2ab − 5c) − (3a² b + 3c) =
= 2ab − 5c − 3a² b − 3c =
= −3a² b + 2ab − 8c.
, .6x (x³ − 2) =
= 6x × x³ − 6x × 2 =
= 6x4 − 12x.
, .(2a − b) × (3a − 4b) =
= 6a² − 8ab − 3ab 4b² =
= 6a² − 11ab + 4b².
, .

| | | 㳿 | |
, Ctrl+Enter

© 2008-2022. - 2

 
[
]